1978
DOI: 10.1037/0022-006x.46.6.1448
|View full text |Cite
|
Sign up to set email alerts
|

A social-behavioral analysis of skill deficits in delinquent and nondelinquent adolescent boys.

Abstract: Delinquent behavior is conceptualized as a manifestation of situation-specific social-behavioral skill deficits. The research was in two phases. In Phase 1, a measure consisting of 44 behavioral role-playing and problem-solving itemsthe Adolescent Problems Inventory (API)-was empirically developed, along with an item-specific criterion-referenced raters' manual. The inventory was designed to identify strengths and weaknesses in the personal and interpersonal skills repertoires of adolescent boys. Phase 2 was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
143
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(147 citation statements)
references
References 9 publications
2
143
1
Order By: Relevance
“…Recently, Holtzworth-Munroe (1992b) proposed that the problem of intimate abusiveness may be explained using McFall's (1982) socialcognitive model, an explanatory model which has been used extensively in other areas of social skills research. Previously, McFall's model has been used to identify social skills deficits in populations including depressed college males (Fisher-Beckfield & McFall, 1982), psychiatric inpatients (Goldsmith & McFall, 1975), delinquent adolescent boys (Freedman, Rosenthal, Donahoe, Schlundt, & McFall, 1987;Holtzworth-Munroe, 1992b), rapists (Lipton, McDonel, & McFall, 1987;McDonel & McFall, 1991), and aggressive boys (Dodge & Coie, 1987). According to the model, "social skills are ... the specific abilities that enable a person to perform competently at particular social tasks" (McFall, 1982, p. 23).…”
Section: Differences In Coping Strategiesmentioning
confidence: 99%
“…Recently, Holtzworth-Munroe (1992b) proposed that the problem of intimate abusiveness may be explained using McFall's (1982) socialcognitive model, an explanatory model which has been used extensively in other areas of social skills research. Previously, McFall's model has been used to identify social skills deficits in populations including depressed college males (Fisher-Beckfield & McFall, 1982), psychiatric inpatients (Goldsmith & McFall, 1975), delinquent adolescent boys (Freedman, Rosenthal, Donahoe, Schlundt, & McFall, 1987;Holtzworth-Munroe, 1992b), rapists (Lipton, McDonel, & McFall, 1987;McDonel & McFall, 1991), and aggressive boys (Dodge & Coie, 1987). According to the model, "social skills are ... the specific abilities that enable a person to perform competently at particular social tasks" (McFall, 1982, p. 23).…”
Section: Differences In Coping Strategiesmentioning
confidence: 99%
“…There is limited evidence that both male and female delinquent populations may suffer from deficits in social skills/social competence (Freedman et al, 1978;Spence, 1981; Gaffney and McFall, 1981); however it is not established that such deficits may be a determinant of delinquency.…”
Section: Adolescent Offenders (Delinquents)mentioning
confidence: 99%
“…Results revealed that where high levels of aggression were shown in 8 year olds, aggression remained stable at 19 and 30 years of age, including acts of criminality (e.g., r = .30, p < .001, n = 190, MMPIS; and r = .29, p < .001, n = 193, self-report). Impulsivity is viewed as an absence of information processing between impulse and action (Ross & Fabiano, 1985), exhibiting a lack of self-control (Gottfredson & Hirschi, 1990) resulting from social skills deficits (Freedman, Rosenthal, Donahoe, Schlundt, & McFall, 1978).…”
Section: Theme 1: Trait-driven Behaviorsmentioning
confidence: 99%